Three-dimensional trapping and manipulation of a Mie particle by hybrid acoustic focused petal beams - Luo, Yan-Chun (2023)
Acoustic manipulations of microparticles have significant implications in physics, chemistry, biology, and biomedicine. For large Mie particles, both the scattering force and the gradient force affect the trapping and manipulation behaviors, and thus, a passive acoustic tweezer (AT) for three-dimensionally manipulating a Mie particle remains challenging. Here, a passive AT based on a hybrid acoustic artificial plate is proposed to generate a hybrid acoustic focused petal beam (HAFPB) for capturing and manipulating a Mie microparticle in three dimensions. In the HAFPB, a lateral acoustic focused petal beam and an axial bifocal acoustic beam (BAB) combine to create a central zero-intensity zone for particle trapping, which can be adjusted by modulating the topological charge of the HAFPB. The acoustic radiation forces (ARFs) acting on large Mie particles with different diameters are investigated. The ARFs on the polystyrene sphere are greatly influenced by the particle size. If the particle is larger than the central zero-intensity zone, an AT with a larger topological charge and a stronger BAB is required for trapping and manipulating this larger particle. Finally, the experiments demonstrate that the AT can stably trap and manipulate a large Mie particle in three dimensions in water.